Analysis of students' competence in chemistry cognitive test construction based on revised bloom's taxonomy. (June 2020) - Ramlawati,; Anwar, M; Yunus, S R; Nuswowati, M
Abstract: The test is one of the tools used to measure the cognitive competence of students. The ability to develop tests is one of the competencies teachers and prospective teachers must possess. Revised Bloom's Taxonomy combines cognitive levels and types of knowledge in constructing cognitive tests. The subject of this study was a postgraduate student in the Chemistry Education Study Program of Makassar State University consisting of 25 people. The purpose of this study was to analyze the students competence in construction of chemistry cognitive tests based on the Revised Bloom's Taxonomy. This research is quantitative descriptive. Analysis of student competency in developing tests is measured by the test suitability indicators with cognitive levels and types of knowledge. The results of the analysis show that the students competence percentage construction questions level C1, C2, C3, C4, C5, C6 respectively: 98%, 89%, 96%, 89%, 65%, and 60%. The percentage of students competence in tests construction according to the type of knowledge, respectively for the types of factual, conceptual, procedural, and metacognitive knowledge are 84%, 83%, 85%, and 83%. Thus it can be concluded that the student competences in constructing of Chemistry cognitive test based on Revised Bloom's Taxonomy is in a good category.